Advancing Neuromodulation Through Control Systems: A General Framework and Case Study in Posture‐Responsive Stimulation. (June 2014) - Denison, Timothy; Litt, Brian
Abstract : Objectives: To provide a general control system framework for neuromodulation, its practical challenges, and historical underpinnings in cardiac rhythm devices, and to illustrate the potential of closed‐loop techniques in neuromodulation with a case study using an adaptive neural stimulation system that integrates sensing, actuation, and state estimation for the treatment of chronic pain through spinal cord stimulation. Materials and Methods: The current state of neuromodulation can be viewed in a classical dynamic control framework: the nervous system is the classical "plant, " the neural stimulator is the actuator, tools to collect clinical data are the sensors, and the physician's judgment is the state estimator and mechanism for closing the therapy feedback loop. This framework highlights the opportunities available to advance neuromodulation. Results: Technology has the capability to address key factors limiting the performance of current systems: observability, the ability of the device to monitor the state of the nervous system from sensor‐based measurements in real time; and controllability, the ability of the device to drive the nervous system to a desired physiological state using suitable algorithms and actuation. Conclusions: Technological advances in neuromodulation using such a control framework have the potential to improve neurologic therapies. Future opportunities for extending the role of these systems are briefly discussed.